Satir Resistensi Kebijakan Covid 19 Di Twitter - Irwanto, Irwanto; Hariatiningsih, Laurensia Retno; Ningtyas, Dito Anjasmoro (Universitas Bina Sarana Informatika, 2023)
This paper is motivated to reveal the satirical messages of netizens on Twitter social media regarding their resistance to Covid 19 policies and rules. Descriptive qualitative is used as a method to answer the main problem in this research. The research subjects were determined through purposive techniques on satirical tweets of netizens regarding Covid 19 policies and rules. Data analysis is carried out with MAK Halliday's social semiotics and the elaboration of the results with the theory used. Through this method, researchers can find out, understand and comprehensively describe the satirical messages about Covid 19 policies and rules constructed by netizens. In this context, the satirical messages constructed in netizen tweets are part of the creativity in message packaging. The communication symbols used are diverse. Communication motives in the form of criticism or suggestions, ideas, and opinions of netizens can be packaged in the form of satire. It takes enough reasoning and knowledge to be able to digest the full meaning of satire. Constructing messages with satire is an alternative choice so that messages can be effective, received comfortably, and avoid legal sanctions.